Communication in the Era of Artificial Intelligence: Its Impact on Human-Technology Interaction - Rina Sovianti; Novrian Novrian (PT. Anagata Sembagi Education, 2024)
In the increasingly advanced digital era, artificial intelligence (AI) has changed the way we interact with technology and with each other. This study aims to explore the impact of artificial intelligence on human communication, as well as how this technology affects the dynamics of social and professional interactions. This study uses a qualitative approach with literature analysis and in-depth interviews with technology and communication practitioners in Indonesia. The results of the study show that artificial intelligence has a significant impact on increasing communication efficiency, but also brings challenges in terms of emotional relationships and privacy. The impact of artificial intelligence on human communication is very visible in various aspects of life, both in the professional and social worlds. The use of AI in chatbots, recommendation systems, and virtual assistants has accelerated the communication process, but also raises questions about its impact on the authenticity and quality of relationships between people. This study identifies the main challenges faced by Indonesian society in adapting to this new technology, including limited technological literacy and concerns about privacy. Overall, this study reveals the importance of managing communication more wisely amid the rapid development of artificial intelligence. Although this technology provides many benefits, organizations and individuals need to be aware of the potential risks that can arise, such as over-reliance on AI or negative impacts on more personal social interactions. This research is expected to provide deeper insights for communication practitioners, technology developers, and the wider community in facing communication challenges in the era of artificial intelligence.